Airway and systemic effects of hydrofluoroalkane fluticasone and beclomethasone in patients with asthma - Currie, G (BMJ Group, 2002)
Background: With the transition to hydrofluoroalkane-134a propellants in metered dose inhalers, it is important to consider the efficacy and safety profiles of formulations containing inhaled corticosteroids. We examined the airway and systemic effects of hydrofluoroalkane-134a fluticasone propionate (FLU-HFA) and beclomethasone dipropionate (BEC-HFA) at recommended labelled doses. Methods: Twenty mild to moderate asthmatics were randomised in crossover fashion to receive 6 weeks of 500 µg/day followed by 1000 µg/day FLU-HFA and BEC-HFA. Measurements were made at baseline after placebo run in and washout, and after each randomised treatment. The primary airway outcome for benefit was the dose of methacholine provoking a fall in forced expiratory volume in 1 second (FEV(1)) of 20% or more (methacholine PD(20)) and for systemic adverse effects was overnight urinary cortisol/creatinine (OUCC). Results: For mean responses, both doses of BEC-HFA and FLU-HFA produced significant improvements in PD(20) compared with baseline. The improvement was not significantly greater with 1000 µg/day FLU-HFA versus BEC-HFA, a 1.69 fold difference (95% CI 0.94 to 3.04). Both doses of BEC-HFA but not FLU-HFA caused significant suppression of OUCC compared with baseline, with significantly (p<0.05) lower values at 1000 µg/day for BEC-HFA versus FLU-HFA (1.97 fold difference (95% CI 1.28 to 3.02)). Conclusion: There was no difference in the airway and systemic effects in patients with mild to moderate asthma between FLU-HFA and BEC-HFA at a dose of 500 µg/day. At 1000 µg/day there was increased systemic bioactivity with BEC-HFA compared with FLU-HFA, without any gain in airway efficacy.